Estratégias de ensino balizadas pela aprendizagem em ação: um estudo no curso de Graduação em Administração da Universidade Federal da Paraíba - Lima, Thales Batista de (2011)
This study had as objective to analyze the diffusion of teaching strategies buoyed by the perspective of action learning in the graduate course in Business Administration at the Federal University of Paraíba. To achieve this purpose was established the following specific objectives: a) Characterize the perspective of learning used by teachers in the teaching of subjects of the formation professional in the course of Administration of the UFPB b) Identify the teaching strategies used by teachers in the teaching of subjects of the formation professional in the course of Administration of the UFPB c) Identify the use of the teaching-in-action strategies by teachers in the teaching of subjects of the formation professional in the course of Administration of the UFPB. To understand the subject of the work was carried out the theoretical basis that approach adult education, self-directed learning, transformative learning, action learning, strategies teaching for higher education and teaching-in-action strategies (case method, PBL - problem based learning, simulations and business games). The work was guided by the interpretive paradigm and used a qualitative approach, since the researcher is interested in analyzing the diffusion of teaching strategies from the meanings constructed by the research subjects, from their experiences. The study was conducted with ten teachers of the undergraduate course in Business Administration UFPB through interviews that after transcribed, supported the categorization of speech to perform the analysis process, which was structured around the following themes: perspectives of learning, teaching strategies, teaching-in-action strategies and the specific teaching-in-action strategies. The latter was developed from the reports of teachers about the characteristics identified as essential and limiting for their teaching action. These characteristics are those identified in the teaching-in-action strategies that are similar to the perspectives of action learning. Each theme has several interrelated categories that result from the meanings of the speeches analyzed using basic qualitative study. The results of the work revealed that teachers adopt traditional teaching strategies, more expository and sometimes unaware of the teaching-in-action strategies. They indicate some factors for non-adoption, such as lack of institutional support and governmental, the lack of resources and of structure, lack of knowledge of teachers about such strategies, the limited time, the disinterest of the teacher and student and immaturity the student. With this, the teachers surveyed suggest some elements that can support the dissemination of teaching- in-action strategies as the engagement of all in the learning process, conducting educational meetings, culture change and the incentive of interdisciplinarity. Thus, the learning process may result in the transformation of meaning perspectives of students. Finally, some implications and recommendations were present to contribute to the development of studies involving teaching strategies related to other dimensions of the action learning system and to promote improvements in the quality of higher education in business administration.